Consumers’ attitude toward the Food Safety Certificate (FSC) in Malaysia - Mohd Nawi, Nolila; Mohd Nasir, Nurul Izati (Routledge, 2014)
Consumers are becoming selective in food purchasing due to concerns over food safety. Cleanliness, safety, and nutrition are among the desirable food characteristics sorted out by consumers. The Food Safety Certificate (FSC) has been found to be detrimental to the increase in the level of consumer confidence on the safety of food products available in markets. This study investigates consumers’ attitude toward FSC while purchasing food products in Malaysia. The data collected from 350 respondents through a face-to-face survey were analyzed using descriptive and factor analysis methods. The results of the study indicated that the majority of consumers are aware of the FSC function and existence in food products. Factor analysis identified brand, trust, health consciousness, and environmental consciousness as factors associated by consumers with FSC. The results indicate that FSC not only ensures consumer trust on food safety but also helps producers in operation streamlining and quality management.